2017
DOI: 10.1103/physrevlett.119.176808
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic Vibrational Damping of Molecular Adsorbates: Insights into Electronic Friction and the Role of Electronic Coherence

Abstract: We present a perturbation approach rooted in time-dependent density-functional theory to calculate electron-hole (e-h) pair excitation spectra during the nonadiabatic vibrational damping of adsorbates on metal surfaces. Our analysis for the benchmark systems CO on Cu(100) and Pt(111) elucidates the surprisingly strong influence of rather short electronic coherence times. We demonstrate how in the limit of short electronic coherence times, as implicitly assumed in prevalent quantum nuclear theories for the vibr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 65 publications
(141 reference statements)
1
29
0
Order By: Relevance
“…[4-7] Such a short lifetime for a high frequency mode (ω=2129 cm -1 ) can only be explained by its nonadiabatic coupling with surface EHPs, because its direct coupling with the low-frequency phonons is unlikely. This nonadiabatic energy dissipation mechanism has been characterized by various theoretical models, [8][9][10][11][12][13][14][15][16][17][18] cumulating with the latest first-principles calculations that quantitatively reproduced the observed lifetime. [19,20] It was thus a surprise when Shirhatti et al reported a long lifetime (~10 2 ps) for trapped CO(ν=1) in the scattering of vibrationally excited CO(ν=2) from Au (111).[21] It was postulated that physisorption might be involved, given the relatively low desorption temperature of CO from Au (111).[22] Indeed, a recent density functional theory (DFT) study by Lončarić et al did find such a physisorption well for CO on Au(111),[23] using the Bayesian Error Estimation Functional method with van der Waals corrections (BEEF-vdW).[24] The lifetime of physisorbed CO(ν=1) was calculated within first-principles many-body perturbation theory and found to be consistent with the experimental value.[21] The long vibrational lifetime was attributed to the weaker couplings with EHPs because of the large distance between the adsorbate and surface.…”
mentioning
confidence: 99%
“…[4-7] Such a short lifetime for a high frequency mode (ω=2129 cm -1 ) can only be explained by its nonadiabatic coupling with surface EHPs, because its direct coupling with the low-frequency phonons is unlikely. This nonadiabatic energy dissipation mechanism has been characterized by various theoretical models, [8][9][10][11][12][13][14][15][16][17][18] cumulating with the latest first-principles calculations that quantitatively reproduced the observed lifetime. [19,20] It was thus a surprise when Shirhatti et al reported a long lifetime (~10 2 ps) for trapped CO(ν=1) in the scattering of vibrationally excited CO(ν=2) from Au (111).[21] It was postulated that physisorption might be involved, given the relatively low desorption temperature of CO from Au (111).[22] Indeed, a recent density functional theory (DFT) study by Lončarić et al did find such a physisorption well for CO on Au(111),[23] using the Bayesian Error Estimation Functional method with van der Waals corrections (BEEF-vdW).[24] The lifetime of physisorbed CO(ν=1) was calculated within first-principles many-body perturbation theory and found to be consistent with the experimental value.[21] The long vibrational lifetime was attributed to the weaker couplings with EHPs because of the large distance between the adsorbate and surface.…”
mentioning
confidence: 99%
“…The ensuing theoretical efforts aimed to comprehend these experimental observations are remarkable. In particular, the nonadiabatic relaxation of vibrationally excited adsorbates is most commonly studied either by * dino.novko@gmail.com relaxation-rate calculations based on first-order perturbation theory [15][16][17][18][19] or by performing molecular dynamics with the corresponding electronic friction [20,21]. In the former case, the intermode coupling is usually tackled by including an additional damping rate due to direct anharmonic coupling [22,23].…”
mentioning
confidence: 99%
“…A number of computational tools for studying nonadiabatic processes of adsorbates on metal surfaces exist in the literature. Time dependent density functional theory algorithms for evaluating electron–hole pair excitations have been successfully applied to a number of systems . Similarly, molecular dynamics with electronic friction algorithms have been applied to obtain vibrational lifetimes of adsorbates on surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…Time dependent density functional theory algorithms for evaluating electron-hole pair excitations have been successfully applied to a number of systems. [18][19][20] Similarly, molecular dynamics with electronic friction algorithms [21,22] have been applied to obtain vibrational lifetimes of adsorbates on surfaces. [21][22][23] Despite the success and simplicity of the electronic friction approach, its applicability to describe the experimental results for NO scattering from noble metal surfaces obtained by Wodtke and Co. [3,24] has been questioned.…”
Section: Introductionmentioning
confidence: 99%